Complementary irrigation and direct drilling have little effect on soil organic carbon content in semiarid Argentina - Giubergia, Juan Pablo (2013)
Irrigation and tillage modify soil properties. The aim of the present study was to evaluate the simultaneous effect of complementary irrigation and zero tillage (ZT) on soil organic carbon (SOC). Two treatments (irrigated and rain fed soils) were evaluated in a field experiment set up in Manfredi, Córdoba province, Argentina. The soil was grid-sampled at the beginning of the experiment in 1996 and soil organic carbon (SOC), aggregate stability (AS), bulk density (BD), electrical conductivity (EC) and exchangeable sodium percentage (ESP) were determined in 2007. In the irrigated treatment SOC tended to increase on the surface layer in the irrigated experiment. The increase in SOC stock was estimated as 0.221 tn C/ha/year but higher C-CO2 emission also occurred. The AS of the surface horizon was higher under irrigation, associated with SOC and soil EC. The quasi-equilibrium in SOC was explained by a greater intake of crop residues counteracted by an increased biological activity in the irrigated soil.